Dietary Supplementation of Chitosan Oligosaccharide–Clostridium butyricum Synbiotic Relieved Early-Weaned Stress by Improving Intestinal Health on Pigeon Squabs (Columba livia) - Wen, Jiashu; Zhao, Wenyan; Li, Jiankui; Hu, Caihong; Zou, Xiaoting; Dong, Xinyang (Frontiers in Immunology, 2022)
According to previous study, we had found that early weaning did harm to growth performance, intestinal morphology, activity of digestive enzymes and antioxidant status in pigeon squabs (Columba livia). Chitosan oligosaccharides (COS) and Clostridium butyricum have been reported to have great potential to improve the growth performance and intestinal health of early-weaned animals. Therefore, the aim of this study is to explore whether dietary supplementation with COS-Clostridium butyricum synbiotic could relieve early-weaned stress by evaluating its effects on growth performance and intestinal health in pigeon squabs. A total of 160 squabs (weaned at 7 days of age) were randomly divided into 5 groups: the control group, fed with artificial crop milk; the COS supplementation group, fed with artificial crop milk +150 mg/kg COS; and three synbiotic supplementation groups, fed with artificial crop milk + 150 mg/kg COS + 200, 300 and 400 mg/kg Clostridium butyricum, respectively. The results showed that diet supplemented with COS-Clostridium butyricum synbiotic benefitted the growth performance for early-weaned squabs, even so the differences were not significant among the five groups (P > 0.05). In addition, dietary supplementation of 150 mg/kg COS + 300~400 mg/kg Clostridium butyricum significantly improved the intestinal morphology (especially villus surface area and villus height to crypt depth ratio), activity of digestive enzymes (lipase, trypsin and leucine aminopeptidase) in duodenum contents and the production of total short chain fatty acids and acetic acid in ileum content (P < 0.05). Additionally, dietary supplementation of 150 mg/kg COS + 400 mg/kg Clostridium butyricum benefitted gut health by improving the antioxidant capacity (glutathione peroxidase and total antioxidant capacity) and cytokines status (IL-4 and IL-10) (P < 0.05), as well as improving the intestinal microbiota diversity. In conclusion, our results revealed that dietary supplementation with synbiotic (150 mg/kg COS + 300~400 mg/kg Clostridium butyricum) could relieve early-weaned stress by maintaining intestinal health in pigeon squabs.